„Text Matters”, czyli wokół tekstu: Recenzja magazynu literaturoznawczego Instytutu Anglistyki Uniwersytetu Łódzkiego - Gucio, Katarzyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
The author reviews two issues of „Text Matters: A Journal of Literature, Theory and Culture” that have been published to date. The review discusses the main areas that the Łódź-based publication addresses (literary and cultural studies intersecting with literary theory, gender studies, history, philosophy, and religion), with particular emphasis on the textual aspect of issues raised in the two volumes. The reviewer also discusses individual contributions, pointing to their interdisciplinary and international character.